Chemical reaction dynamics: analysis of the brusselator model - Stonkienė, Liana; Švitra, Donatas (Lietuvos matematikos rinkinys, 2010)
It is observed the differential equations system. The stable periodic solution of the nonlinear differential equations system is constructed, which is based on the theory of bifurcations.
Keywords: Brusselator; nonlinear differential equations; periodic solution